Airway Obstruction in Primary Care Patients: Need for Implementing Spirometry Use - Salvatore Bucchieri; Pietro Alfano; Palma Audino; Giovanni Fazio; Salvatore Marcantonio; Snamid Palermo Cooperative Group; Giuseppina Cuttitta (Diagnostics, 2022)
(1) Background: To detect early airway obstruction in an adult primary care setting. (2) Methods: Seventeen general practitioners (GP) were involved. A total of 912 patients consulting their GPs over 40 years were recruited: 583 of them (323M) agreed to perform/undergo all the procedures: respiratory questionnaire, mMRC questionnaire, and spirometry. We identified four subgroups: physician COPD patients; physician asthma patients; asthma-COPD overlap syndrome patients; and no respiratory diagnosis subjects, on the basis of physician diagnosis. For screening purposes, an FEV1/FVC < 70% was considered a marker of airway obstruction (AO). (3) Results: Prevalence rates of COPD, A, and ACOS were 12.5%, 7.8%, and 3.6%, respectively. In the overall sample 16.3% showed airway obstruction: 26% mild, 56% moderate, 17% severe, and 1% very severe. In obstructed subjects, those reporting neither respiratory symptoms nor a physician’s respiratory diagnosis were 60% level I; 43% level II; 44% level III; and none level IV. Wheezing (p < 0.001), sputum (p = 0.01), older age (p < 0.0001), and male gender (p = 0.002) were the best predictors of airway obstruction. (4) Conclusions: A high prevalence of AO was found. In AO we found a high prevalence of subjects without respiratory symptoms or respiratory chronic diagnosis. Airway obstruction was predicted by the presence of wheezing, sputum, older age, and male gender.